(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
The potential allelopathic effect of a green walnut fruit extract on seed germination and early growth of three weed species (Chenopodium album, Amaranthus retroflexus, Daucus carota) was tested, as well as its phytotoxic effect on seed germination and early growth of maize (Zea mays). Another objective was to analyze the plant extract and assess its antioxidative activity. Antioxidative activity of the plant extract was evaluated based on its ability to neutralize DPPH (2,2-diphenyl-1-picrylhydrazyl) radical and capacity for iron reduction using the FRAP method. Inhibition of the evaluated parameters (total germination and seedling length) decreased proportionally with decreasing concentrations of extract solution of green walnut fruit. The parameters of seedling growth were also found to show greater susceptibility than total seed germination of all three of the tested weed species. Although the seed bioassay results indicated a high inhibitory effect on germination and early growth of the tested weeds, they also revealed phytotoxic activity during early growth of the cultivated Z. mays.